Cerebral amyloid angiopathy: A case report - Bharti Saini (International Journal of Medical Research and Review, 2018)
Cerebral amyloid angiopathy (CAA) is a cerebrovascular disorder caused by the accumulation of cerebral β amyloid (Aβ) in the media and intima of leptomeningeal and cortical vessels of the brain. The resultant vascular fragility tends to manifest in normotensive elderly patientsas lobar intracerebral hemorrhage and is a common cerebral amyloid deposition disease.